Automatic Water Quality and Fish Feed Monitoring System in Aquarium Using LORA - Muhammad Fariz Ilmi; Syamsudduha Syahrorini; Shazana Dhiya Ayuni (Journal of Computer Networks, Architecture and High Performance Computing, 2023)
Keeping ornamental fish, especially guppies, is a type of ornamental fish that is widely kept because it has a very beautiful color pattern. The growth of guppies is influenced by environmental factors, including water temperature, water pH, and water turbidity. Fish feed is also a very important factor in the survival of fish. In general, the ideal temperature that can make guppies develop well between the range of 23-27 °C, the pH of the water is in the range of 6-8 pH. and the turbidity of guppy water requires a water turbidity level of 0-25 NTU. The purpose of this study is to design and create a water quality monitoring system in guupies using LoRa and automatic feeding according to realtime. The hardware used is Arduino Uno as a microcontroller, LoRa SX1278 as long-distance communication, Turbidity Sensor, DS18B20 temperature sensor, water pH sensor as LCD 16x4, RTC, Relay, Water pump. The system created can monitor the water temperature, water turbidity level, and Ph of aquarium water automatically. Testing is carried out by detecting the quality of aquarium water with all sensors simultaneously to determine the condition of the water which will later be monitored using LoRa. The test results determine if the water state is cloudy with a range of >2000 NTU, the water pump will automatically turn on until the water state reaches the range of <2000 NTU.